High Throughput Discovery of Novel Diagnostic Antigens for Mycobacterium bovis Using a Whole Genome Approach - Assal, Nadia (Université d'Ottawa / University of Ottawa, 2021)
Bovine tuberculosis (BTB) is a chronic infectious disease caused by the bacterium Mycobacterium bovis. It infects animals and can be a source of zoonosis. In the last five years, Canada has faced two outbreaks of bovine tuberculosis in the years 2018 and 2016. BTB is mainly diagnosed using the Tuberculin skin test, a test that detects the cellular immune response to administered purified protein derivative (PPD). A drawback of this test is the high level of false-positive test results caused by the immune response to PPD proteins that are conserved in non-tuberculous mycobacteria. Current serodiagnostic tests can detect the disease especially in the advanced state with, low sensitivity ranging between 9-45%. It is hypothesized that the profiling of the humoral immune responses to selected proteins will lead to the discovery of novel immunogenic protein antigens for improved BTB diagnostic tests. Bioinformatic tools used in this research for the prediction of extracellular or outermembrane proteins from M. bovis genome sequences identified 96 protein candidates. Also, a proteomic study conducted to identify proteins secreted by M. bovis, together with the review of previous proteomic studies of the PPD, led to the identification of an additional 92 protein candidates. A high throughput system was developed to efficiently express and analyze these antigens involving the PCR amplification, in vivo cloning, and in vitro expression of open reading frames (ORFs) coding for selected protein candidates. This was followed by a high throughput recombinant protein purification and a microarray analysis of these purified recombinant proteins with sera from M. bovis-infected animals. The system successfully amplified, cloned, and expressed 159 recombinant proteins. From the microarray screening, 13 antigens exhibited immunological reactions and were able to differentiate the sera of the infected animals from the controls. Out of those 13 antigens, 4 novel antigens Mb2740c, Mb0598c, Mb3469c, and Mb3453c, in addition to two well-known antigens MPB70 and MPB83, gave the highest reactivity; they were selected for further evaluation for diagnostic applications using ELISA and dot blot assays. Two antigens Mb3469c and Mb3453c had a significant ability to differentiate between infected and control cattle as tested in ELISA and dot blot assays, respectively and demonstrated by ROC curve analysis. These two novel antigens could be added to the panel of serodiagnostic antigens for improving BTB serodiagnosis and could be beneficial in the detection of outbreaks caused by certain M. bovis strains.
Keywords: Mycobacterium bovis; Serodiagnostics; Novel antigens